Chronic thoracic pain after cardiac surgery: role of inflammation and biomechanical sternal stability - Madjarov, Jeko M.; Katz, Michael G.; Hadas, Yoav; Kim, Sofia Jisoo; Freage-Kahn, Lina; Madzharov, Svetozar; Vincek, Adam; Madjarova, Sophia J.; Seidman, Piers; Shtraizent, Nataly; Robicsek, Steven A.; Eliyahu, Efrat (Frontiers in Pain Research, 2023)
Introduction The pathogenesis of chronic chest pain after cardiac surgery has not been determinate. If left untreated, postoperative sternal pain reduces the quality of life and patient satisfaction with cardiac surgery. The purpose of the study was to examine the effect of chest inflammation on postoperative pain, risk factors for chronic pain after cardiac surgery and to explore how chest reconstruction was associated with the intensity of pain. Methods The authors performed a study of acute and chronic thoracic pain after cardiac surgery in patients with and without sternal infection and compared different techniques for chest reconstruction. 42 high-risk patients for the development of mediastinitis were included. Patients with mediastinitis received chest reconstruction (group 1). Their demographics and risk factors were matched with no-infection patients with chest reconstruction (group 2) and subjects who underwent conventional sternal closure (group 3). Chronic pain was assessed by the numeric rating scale after surgery. Results The assessment of the incidence and intensity of chest pain at 3 months post-surgery demonstrated that 14 out of 42 patients across all groups still experienced chronic pain. Specifically, in group 1 with sternal infection five patients had mild pain, while one patient experienced mild pain in group 2, and eight patients in group 3. Also, follow-up results indicated that the highest pain score was in group 3. While baseline levels of cytokines were increased among patients with sternal infection, at discharge only the level of interleukin 6 remained high compared to no infection groups. Compared to conventional closure, after chest reconstruction, we found better healing scores at 3-month follow-up and a higher percentage of patients with the complete sternal union. Conclusions Overall, 14 out of 42 patients have chronic pain after cardiac surgery. The intensity of the pain in mediastinitis patients significantly decreased at 3 months follow-up after chest reconstruction. Thus, post-surgery mediastinitis is not a determining factor for development the chronic chest pain. There is no correlation between cytokines levels and pain score except interleukin 6 which remains elevated for a long time after treatment. Correlation between sternal healing score and chronic chest pain was demonstrated.